On the formation of mixed ordered structures in the coadsorption system benzene + NO on Ni(111) - Zebisch, P.; Huber, W.; Steinrück, Hans-Peter (Surface Science, 1991)
The adsorption, desorption and ordering behavior of coadsorbed benzene + NO layers on Ni(111) have been studied by TPD and LEED. With increasing NO exposure dissociation of benzene upon heating is more and more suppressed and molecular benzene desorption is observed in a variety of peaks between 370 and 440 K which strongly depend on the initial benzene and NO coverages. Under certain conditions dissociation of benzene can be completely suppressed. The desorption behavior of NO is essentially unchanged as compared to NO desorption from the bare Ni(111) surface. Depending on initial benzene and NO coverage four ordered benzene + NO structures have been observed: (2 3×2 3)R30 °, (3 × 3), c(2 3×4)rect and (2 3×4 3) R30 °. In all cases the coadsorbed layers were disordered after adsorption at 120 K and ordering was only observed after annealing to 250 K. The observed structures can be correlated to different molecular benzene desorption peaks. The formation of the various ordered benzene + NO structures and their correlation to the TPD spectra is discussed. © 1991.